1997
DOI: 10.1038/sj.ejcn.1600470
|View full text |Cite
|
Sign up to set email alerts
|

Age at introduction of complementary food and physical growth from 2 to 9 months in rural Senegal

Abstract: Objective: To compare nutritional status and physical growth among infants according to age at introduction of complementary food (CF). Design: A longitudinal observational study. Setting: Three health clinics in a rural area of Senegal. Subjects: During immunization sessions, 522 infants were recruited at 2±3 months. Complete data on three visits were available for 420 infants (4 visits: n 361); 73 were lost to follow-up and 29 had incomplete data. Main outcome measures: Increments in length and weight betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 7 publications
3
30
0
2
Order By: Relevance
“…According to this reference, Tibetan children were offered complementary foods so early, mainly cereals such as Zanba and porridge. Studies suggested that earlier complementary feeding seemed not to improve younger child growth and nutritional status significantly compared with exclusive breastfeeding for 6 months (Cohen et al, 1994;Haider et al, 1996;Simondon & Simondon, 1997;Dewey et al, 1998Dewey et al, , 1999, but might decrease intake of breast milk and increase risk of morbidity such as gastrointestinal infection (Brown et al, 1989;Popkin et al, 1990;Oddy et al, 1999;Hornell et al, 2001). However, there have been not evaluation of effect of early introduction of Zanba on Tibetan child nutrition and health.…”
Section: Discussionmentioning
confidence: 99%
“…According to this reference, Tibetan children were offered complementary foods so early, mainly cereals such as Zanba and porridge. Studies suggested that earlier complementary feeding seemed not to improve younger child growth and nutritional status significantly compared with exclusive breastfeeding for 6 months (Cohen et al, 1994;Haider et al, 1996;Simondon & Simondon, 1997;Dewey et al, 1998Dewey et al, , 1999, but might decrease intake of breast milk and increase risk of morbidity such as gastrointestinal infection (Brown et al, 1989;Popkin et al, 1990;Oddy et al, 1999;Hornell et al, 2001). However, there have been not evaluation of effect of early introduction of Zanba on Tibetan child nutrition and health.…”
Section: Discussionmentioning
confidence: 99%
“…One study in rural Senegal reported similar findings that infants complemented at 2-3 months of age had significantly lower length for age and weight for length. 28 However, one intervention study in Honduras did not find growth differences between children introduced to CFs at 4 and 6 months of age. 7 We inferred that these controversial findings might be partly because of the maternal breast-feeding performance and the quality and safety of CFs.…”
Section: -26mentioning
confidence: 96%
“…Our analyses also indicate that the use of other foods during this period was not associated with any differences in growth, although children who were fed more complementary foods had higher rates of diarrhea. Other longitudinal studies have also shown either no difference in growth or a negative association between complementary feeding and growth from 4 to 6 months (Kusin et al, 1991;Martines et al, 1994;Simondon & Simondon, 1997;Zumrawi et al, 1987).…”
Section: Growth Predictors Of Ghanaian Infantsmentioning
confidence: 98%